mGFD: A Meshless Generalized Finite Difference Method ... - Tinoco-Guerrero, Gerardo; Domínguez-Mota, Francisco Javier; Guzmán-Torres, José Alberto; Pedraza-Jiménez, Gabriela; Tinoco-Ruiz, José Gerardo (Code Ocean, 2025)
# mGFD: A Meshless Generalized Finite Difference Method Data and methods for numerically solving Partial Differential Equations using a meshless Generalized Finite Differences Scheme. All the codes are distributed under MIT License on [GitHub](https://github.com/gstinoco/mGFD) and are free to use, modify, and distribute giving the proper copyright notice. ## Description This repository proposes a way to achieve approximations to various Partial Differential Equations in two dimensions on highly irregular regions. For this, the proposed method uses a Generalized Finite Differences Method for the numerical solution on unstructured clouds of points. ## Data All the data were taken from Author's [Cloud-Generation Github Repository](https://github.com/gstinoco/Cloud-Generation). The data is free for anyone to use to compare the results using different methods with the same dataset. The following regions were considered for this repository: - **BAN**: Banderas bay in Mexico. - **BLU**: Blue Lagoon in Iceland. - ...